Edukasi Simulasi Dan Pencegahan Pergaulan Negatif Pada Lingkungan Sekolah SMK Fajar Ciseeng, Jl. Fajar, RT.007/RW003, Kelurahan Babakan, Kecamatan. Ciseeng, Kabupaten Bogor, Jawa Barat 16120 - Mulya Febri Andini; Asya Pebria Jahra; Nabila Rhea Audrysca; Irfan Rizka Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Community Service Activities (Pengabdian kepada Masyarakat/PKM) are one form of implementation of the Tri Dharma of Higher Education, aiming to apply knowledge in a concrete way within society. This PKM activity adopts the theme “Educational Simulation and Prevention of Negative Social Interaction in the School Environment”, targeting twelfth-grade students of SMK Fajar Ciseeng. The background of this activity is the increasing challenges faced by adolescents in dealing with negative influences such as bullying, promiscuity, misuse of social media, and behavioral deviations resulting from a lack of emotional management and self-control. The methods used include material presentations, interactive discussions, case simulations, question-and-answer sessions, and the writing of impressions and messages to obtain feedback from participants. The results of the activity indicate that students gained a better understanding of the importance of controlling emotions, being critical in the use of social media, and building a positive, bullying-free school environment. Therefore, this PKM activity has a positive impact on increasing students’ awareness and behavior in preventing negative social interactions.